Application of silicon and biochar alleviates the adversities of arsenic stress in maize by triggering the morpho-physiological and antioxidant defense mechanisms - Sattar, Abdul; Sher, Ahmad; Abourehab, Mohammed A. S.; Ijaz, Muhammad; Nawaz, Muhammad; Ul-Allah, Sami; Abbas, Tahira; Shah, Adnan Noor; Imam, Mohamed S.; Abdelsalam, Nader R.; Hasan, Mohamed E.; Abbas, Aown; et al. (Frontiers in Environmental Science, 2022)
Arsenic (As) contamination in soil adversely affects crop productivity, grain quality, and human health. A pot experiment was performed to assess the sole and combined effect of Si and biochar on growth, physiological, antioxidant defense mechanism, yield, and grain quality of maize. Soil treatments comprised of control (no treatment), As (12 mg kg-1 ), Si (100 mg kg-1), biochar (50 g kg-1), Si + biochar (100 mg kg-1 + 50 g kg-1), As + Si (12 mg kg-1 + 100 mg kg-1), As + biochar (12 mg kg-1 + 50 g kg-1) and As + Si + biochar (12 mg kg-1 + 100 mg kg-1 + 50 g kg-1). The experiment was carried out by using the completely randomized design with three replications. The As toxicity significantly reduced chlorophyll a (5.18%), chlorophyll b (33.87%), and chlorophyll a+b (11.67%), primary metabolites (soluble protein (54.93%), amino acids (24.85%), total soluble sugar (39.77%), and phenolic contents (25.88%)) while increased the activities of enzymatic antioxidants like superoxide dismutase (SOD) by 43.51%, peroxidase (POD) by 47.93%, catalase (CAT) by 47.98% and ascorbate peroxidase (APX) by 59.02% in the leaves of maize. Moreover, As stress increased the lipid peroxidation in the form of malondialdehyde (MDA) by 49.24%, and also enhanced the hydrogen peroxide (H2O2) content by 53.13%, electrolyte leakage (EL) by 40.86% as well as proline contents in the leaves. In addition, As contamination reduced the grain yield and yield-related attributes relative to respective no-As treatments. Among the soil applications, Si and/or biochar improved maize grain yield (12.12%) by triggering the activities of enzymatic antioxidants, proline contents, and by reducing the H2O2 and MDA contents. The combined application of Si and biochar enhanced the Si contents in shoots of control and As-contaminated plants while significantly reduced the As concentration in shoots (69%) and grains (142%). In conclusion, the combined application of Si and biochar was found to be a fruitful soil amendment strategy to improve the yield of maize under As-contaminated soil.